Republic of Slovenia : 2011 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; Staff Statement; and Statement by the Executive Director for Slovenia. (IMF Staff Country Reports; Country Report, 2011)
The global crisis exacerbated the Slovenian economy's previous imbalances in the fiscal, financial, and real sectors. The authorities agreed that fiscal consolidation including pension, health care, and financial management is essential for sustainable recovery. The Bank of Slovenia emphasizes that banks' governance and capitalization should be enhanced, regardless of ownership. The authorities suggested that structural reforms in labor and product markets are critical to boost potential growth. The authorities agreed that maintaining competitiveness is crucial for Slovenia as it has a small and export-dependent economy.